Quantifying pre-consumer food and nutrient losses from the Australian lamb and sheep meat value chain: a case study - Wingett, Kate; Alders, Robyn (Frontiers in Sustainable Food Systems, 2024)
To achieve sustainable development, United Nation members have agreed to reduce food loss along the pre-consumer food supply chain. Food loss and waste is a significant challenge facing Australia and the world, with an estimated one third of all food produced locally being lost or wasted. Globally, Australia is the second largest producer of sheep meat and, locally in Australia sheep meat is the second largest meat industry. Previous assessments of Australian livestock industries estimate low levels of food product losses from the sheep meat chain. This case study aimed to quantify nutrient losses at the point of slaughter of Australian lambs and sheep, using a mass balance approach with secondary data. The results from this study align with this previous assessment with respect to the level of products and nutrients downgraded at the point of slaughter, except for the impact of cadmium contamination on adult sheep liver and kidney downgrades. In turn, cadmium contamination emerged as a key contributor to micronutrient losses, notably dietary folate equivalents, and vitamin A retinol equivalents (RE). There was moderate to high uncertainty in the outputs of the assessment, predominantly due to the absence of data. Addressing these challenges, particularly the absence of offal production data, is crucial as it influences the overall accuracy of the results. This study identifies areas for improvement in the Australian sheep meat value chain, including data governance, at both the macro and micro levels. It also serves as a foundational step in understanding how reducing food and nutrient losses in the Australian sheep meat value chain could contribute to food security and nutrition goals.